Prevalence of Bovine Trypanasomosis in Guto Gida District of East Wollega Zone, Oromia Regional State, Ethiopia (Global Journal of Medical Research, 2014)
A cross sectional study was carried out to determine the prevalence of bovine trypanosomosis in five peasant associations of Guto Gida District of East Wollega Zone, Ethiopia from October 2013 to March 2014. From five peasant association, 384 cattle were randomly selected and examined for trypanosomosis. The overall prevalence of bovine trypanosomosis was 7.81% of which Trypanosoma congolense infection was 53.33%, Trypanosoma vivax infection was 30% and Trypanosoma brucei was 16.66% with statistically significant difference (P=0.00). A significant association was observed (P
Keywords: bovine; guto gida; PCV; prevalence; trypanosome